种河滨带生态诱导下的植被生态修复方法 (2018)
本发明涉及人工生态诱导下的植被恢复技术领域，尤其涉及种河滨带生态诱导下的植被生态修复方法，其特征在于，包括以下步骤：S1，在平行于河流流向方向，且与河流主风向成预定的角度的方向布设多条种植带，相邻的两种植带之间布设空闲带；S2，在种植带内播种河滨植物物种；S3，对空闲带土地进行穴状整理，经过河滨植物物种成熟期，在空闲带中形成种子富集穴；S4，对空闲带进行浅式旋耕。将种植带布设于与河流主风向成定的角度的方向，借助河流风力，对种子进行传播，减少人工干扰恢复的痕迹；布设空闲带为种子创造适宜的种子富集穴，工程造价相对较低；扩大河滨植物生长范围，更有利于种子传播，实现对河滨带重新更新和密度控制的目的。 The invention relates to the technical field of vegetation ecological restoration induced by artificial ecology and in particular relates to a vegetation ecological restoration method induced by streamside ecology. The vegetation ecological restoration method induced by streamside ecology is characterized by comprising the following steps distributing a plurality of rows of plantation belts in a direction parallel to a river flow direction and forming a preset angle with a river prevailing wind direction, arranging a free belt between each two adjacent plantation belts, broadcasting streamside plant species in the plantation belts, conducting cave-shaped renovation to the free belt land to form a seed enrichment ca